A surplus of memory : chronicle of the Warsaw Ghetto uprising - Zuckerman, Yitzhak, 1915-1981 (University of California Press, 1993)
In 1943, against utterly hopeless odds, the Jews of the Warsaw Ghetto rose up to defy the Nazi horror machine that had set out to exterminate them. One of the leaders of the Jewish Fighting Organization, which led the uprisings, was Yitzhak Zuckerman, known by his underground pseudonym, 'Antek.' Decades later, living in Israel, Antek dictated his memoirs, which were published in Hebrew as Those Seven Years: 1939-1946.